The great road : - Smedley, Agnes (Monthly Review Press, 1956)
Chu Teh, one of the legendary figures of the Chinese Revolution, was born in 1886. He was commander in chief of the People's Revolutionary Army, and this is the story of the first sixty years of his life. As a supreme commanding general, he was probably unique; surely there has never been another commander in chief who, during his years of service, spun, wove, set type, grew and cooked his own food, wrote poetry and lectured not only to his troops on military strategy and tactics but to women's classes on how to preserve vegetables. Evans Carlson wrote that "Chu Teh has the kindness of a Robert E. Lee, the tenacity of a Grant, and the humility of a Lincoln." More than a biography, this work by a great American woman journalist, who took the account from Chu Teh himself, is a social and historical document of the highest value.